The self-regulatory German health care system between growing competition and state hierarchy - Claus Wendt; Heinz Rothgang; Uwe Helmert (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
This article focuses on the changing role of the state in financing, providing and regulating health care services under the German health care system from 1970-2000. While a reduced role of the state can be observed in terms of financing, our analysis of service provision indicates inconsistent developments. Monetary resource flow analyses indicate a decrease in private service provision as a percentage of total health expenditure, but when analysing the development of health employment we see a growth in "private" health care personnel. The most important changes, however, have taken place in terms of regulation. Since the early 1990s, the traditionally self-regulatory German health care system has simultaneously faced growing competition and state hierarchy. – – Thema des Beitrags ist die sich ändernde Rolle des Staates in der Finanzierung, Leistungserbringung und Regulierung im deutschen Gesundheitssystem zwischen 1970 und 2000. Während sich bei der Finanzierung von Gesundheitsleistungen ein Rückzug des Staates abzeichnet, ergibt die Analyse der Leistungserbringung keinen einheitlichen Trend. Gemessen in Prozent der Gesamtausgaben für Gesundheit zeigt die Untersuchung der monetären Ressourcen eine Reduzierung der privaten Leistungserbringung, wohingegen bei der Analyse des Gesundheitspersonals ein Anstieg der privaten Leistungserbringung zu erkennen ist. Die wichtigsten Änderungen erfolgten allerdings im Bereich der Regulierung. Seit den frühen 1990er Jahren befindet sich das traditionell selbstverwaltete deutsche Gesundheitssystem zunehmend in einer Umklammerung aus staatlicher Regulierung einerseits und Wettbewerb andererseits.
Keywords: 320; Gesundheitswesen; Gesundheitsreform; Gesundheitspolitik; Deutschland